The Effectiveness of Teaching Speaking Through Quizizz for The Eleventh Graders of MA NWDI Rensing Bat - Dzoharat Nabilah Mas (ITScience (Information Technology and Science), 2025)
Many students as English foreign language learners failed in learning to speak English. They must have a strong willingness and mentality to speak smoothly and fluently. English teachers have a high demanded to produce an appropriate method in teaching speaking for their students in the classroom. Speaking will become easier and more effective if an appropriate method is based on students’ ability and era. This study focused on teaching speaking through Quizizz. The research problems were (1) To what extent is the attainment of teaching speaking through Quizizz? (2) To what extent is the effect of using Quizizz in teaching speaking? This study was experimental. It consisted of two groups among 40 students, which were divided into 20 students as the experimental group and 20 as the control group. This study used speaking tests in Quizizz and hypothesis testing. Based on the results, the results showed that pre-test scores in the experimental group had the lowest score was 33 and the highest was 69, while in the post-test, they obtained the lowest score of 57 and the highest was 84. Besides, in the control group, the lowest score was 31 and the highest score was 49, while in the post-test, the lowest score was 43 and the highest score was 65. The Mean scores obtained by the experimental group in pre-test and post-test were 47.8 and 67, with a standard deviation of 8.71 and 7.394. The mean score obtained by the control group in the pre-test and post-test was 6.629 and 5.244. Thus, the T-test was higher than the T-table, which meant teaching speaking through Quizizz could increase students’ speaking ability. The hypothesis was accepted, and the null hypothesis was rejected.